Vaginal metastasis of lung cancer: A case report - Federica Savasta; Michele Giana; Alessandro Libretti; Silvia Genestroni; Daniela Surico; Valentino Remorgida (Elsevier, 2023)
Lung adenosquamous carcinoma (ASC) is a rare biphasic malignant tumor with squamous cell carcinoma (SCC) and adenocarcinoma (AC) components. ASC is reported to be aggressive; the most common metastatic sites are the regional lymph nodes and surrounding areas.A 46-year-old woman was referred to the emergency department with a persistent dry cough. She underwent fibro-bronchoscopy and was diagnosed with an adenosquamous lung carcinoma. Other than pulmonary and lymphatic findings, a total-body computed tomography (CT) examination highlighted a hypodense formation, of about 9 mm, with a cystic appearance, at the level of the vaginal region. A biopsy performed in the posterior vaginal wall highlighted a vaginal wall flap with subepithelial localization of neoplasia, compatible with the pulmonary ASC. Oncologists took charge of the case and the patient commenced medical therapy with entrectinib. Four months later, she developed dyspnea, and high-resolution CT highlighted an increase in the pathological tissue causing bronchial occlusion. The patient underwent endobronchial stent placement and thereafter restarted therapy with entrectinib, previously stopped because of the new symptoms, and was closely monitored.Apparently only one case of vaginal metastasis from pulmonary tumor has been previously reported, and this is the first report of vaginal metastasis from ASC. Although extremely rare, the presence of such metastasis should be considered in women with suspected vaginal neoformations.